Immunogenic and Non-Immunogenic Hyperthyroidism - Als, Claudine; Listewnik, Maria; Rosier, H.; Bartkowiak, Elisabeth (Nuklearmedizin - NuclearMedicine, 1995)
Annual occurrences of immunogenic (IH) and non-immunogenic hyperthyroidism (NIH) between Berne (1976, 1982, 1991) and Szczecin (1973, 1980, 1991) were compared. Out of 21,025 patients referred for thyroid examinations, 10.1% (average) were hyperthyroid. In Berne (former endemic goiter region) and Szczecin (without goiter endemicity) IH occurred in 41% and 68%, NIH in 59% and 32% of hyperthyroid patients, respectively. Within a stable incidence of NIH in Berne, toxic adenomas (TA) decreased from 41% (1976) to 17% (1991) (p <0.005). In Szczecin, where iodine deficiency is in an early stage, the TA frequency did not change significantly: from 24% (1973) to 28% (1991). Increases of TA or of multifocal functional autonomy apparently “mark” incipient or, respectively, decreasing deficiencies in nutritious iodine. Hyperthyroid patients in Berne compared to Szczecin were older, both with IH (54 versus 45 y) and NIH (65 versus 52 y). Age at diagnosis was stable in Berne but increasing (p <0.05) in Szczecin (from 43 to 52 y).
Keywords: Hyperthyroidism; iodine deficiency epidemiology; multinodular toxic goiter